2018
DOI: 10.1111/jopr.12911
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Failure Load of Lithium Disilicate Restorations Cemented on a Chairside Titanium‐Base

Abstract: Purpose To evaluate the fatigue failure load of distinct lithium disilicate restoration designs cemented on a chairside titanium base for maxillary anterior implant‐supported restorations. Materials and Methods A left‐maxillary incisor restoration was virtually designed and sorted into 3 groups: (n = 10/group; CTD: lithium disilicate crowns cemented on custom‐milled titanium abutments; VMLD: monolithic full‐contour lithium disilicate crowns cemented on a chairside titanium‐base; VCLD: lithium disilicate crowns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…The results of the present study do not agree with these authors [52], because analyzing a ceramic restoration on fatigue, the screw access hole sealed with composite resin does not increase the generated stresses in the cervical region or decrease the restoration characteristic strength. Supporting the results found in the present study, previous authors [20,21,45] reported that groups with screw access holes showed similar load to failure to the groups without access holes. In addition, the authors suggested that perforated crowns may be even more resilient than groups without the access hole.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the present study do not agree with these authors [52], because analyzing a ceramic restoration on fatigue, the screw access hole sealed with composite resin does not increase the generated stresses in the cervical region or decrease the restoration characteristic strength. Supporting the results found in the present study, previous authors [20,21,45] reported that groups with screw access holes showed similar load to failure to the groups without access holes. In addition, the authors suggested that perforated crowns may be even more resilient than groups without the access hole.…”
Section: Discussionsupporting
confidence: 92%
“…The survival probability of restorations using Tibase as a connection between the implant and the crown is still scarce in the scientific literature [28,45,46]. The indication of this technique depends on the use of CAD/CAM blocks for implant solution that present a connective hole (screw access hole) created by the manufacturer [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations